JYP Entertainment Expansion to International Markets: USA, China, and Japan - Salsabil Febriliana Rafrida; Megahnanda Alidyan Kresnawati (Universitas Muhammadiyah Malang, 2022)
This paper aims to explain JYP Entertainment's business expansion to the USA, China, and Japan markets. JYP Entertainment is one of the major companies in the Korean entertainment industry that participates in producing and distributing Hallyu content to the global market. JYP Entertainment is known to be very ambitious in expanding its market overseas. Some of his artists have succeeded in gaining high popularity in the domestic and foreign markets. Therefore, JYP Entertainment believes in expanding its market to the USA as the first step by establishing JYP USA. Then establishing a subsidiary in China, namely JYP China and JYP Japan in Japan. The establishment of these three different host country subsidiaries had different results. Some have succeeded and benefited from the host country's localization agenda and some have failed until the JYP Entertainment subsidiary had to stop operating. This paper tries to explain the case study using the theory of multidomestic strategy. The author uses descriptive research methods and qualitative data analysis techniques.